SEED HANDLING TECHNOLOGY AND STORAGE BEHAVIOUR OF SALES RETURN SEED UNDER COLD STORAGE CONDITIONS IN MAIZE (Zea mays L.) - K. RAGHAVENDRA; S.N.C.V.L. PUSHPAVALLI, A. AKHIL REDDY1, P. SUJATHA, P. JAGAN MOHAN RAO, A. NOOKA RAJU (The Journal of Research, PJTSAU, 2023)
An experiment to know effect of handling technology on storage behaviour of sales return maize seed after 2 months of cold storage was conducted during 2020 and 2021 in cold storage unit of Kaveri Seed Company Limited. Maize seed of 218+ and Profit each with three different lots, Fresh seed, one time and two times sales returned seeds (Q3) were packed in 4 different packing materials, transported and stored at retailer stores for different months (one, two & three months) under ambient conditions. After completion of predetermined interval seed was brought back, stored for 2 months under cold storage and its effect on seed moisture content (SMC) and seed germination (SG) were recorded. Fresh and One time sales returned seed of 218+ showed significantly low SMC (11.3 and 11.3%). But two times sales returned seed of 218+ and Profit hybrids showed significantly high SMC (11.5 and 11.8 %). Seed of 218+ and Profit packed in Savegrain (P2), Polypouch (P1) and Triple layer bag (P3) recorded significantly lower pooled mean SMC (11.2, 11.3 and 11.3 %) when compared to Recyclable (P4) bag (11.6 and 11.4 %, respectively). Fresh and One time sales returned seed of 218+ hybrid showed significantly high seed germination (95 and 95%) compared to two times sales returned seed (53%). Seed of 218+ packed in Savegrain (P2), Polypouch (P1) and Triple layer bag (P3) recorded significantly higher pooled mean seed germination (82, 81 and 81 %) when compared to Recyclable bag (80%). Profit seed recorded significantly high seed germination (92%) even after 3 months of storage at retailer. Whereas 218+, recorded higher SG (83 %) only for one month at retailer.